Comprehensive Physiology 2019
DOI: 10.1002/cphy.c180012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Functional Differentiation of the Diaphragm Muscle of Mammals

Abstract: Symmorphosis is a concept of economy of biological design, whereby structural properties are matched to functional demands. According to symmorphosis, biological structures are never over designed to exceed functional demands. Based on this concept, the evolution of the diaphragm muscle (DIAm) in mammals is a tale of two structures, a membrane that separates and partitions the primitive coelomic cavity into separate abdominal and thoracic cavities and a muscle that serves as a pump to generate intra-abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 681 publications
6
55
0
1
Order By: Relevance
“…Furthermore, in mouse lumbar MNs, the smaller MNs tend to have less elaborate dendritic arbors than larger MNs, which have more extensive dendritic arborization (Ma and Vacca‐Galloway, ; Leroy et al, ). The increased dendritic arbor of larger MNs seen in past studies and in the present study, and the consequent increase in relative capacitance of large soma surface area MNs to smaller soma surface area MNs is entirely consistent with the Henneman's size principle (Henneman, ; Henneman et al, ; Somjen et al, ; Cullheim and Ulfhake, ; Cullheim et al, ; Heckman and Enoka, ; Fogarty and Sieck, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, in mouse lumbar MNs, the smaller MNs tend to have less elaborate dendritic arbors than larger MNs, which have more extensive dendritic arborization (Ma and Vacca‐Galloway, ; Leroy et al, ). The increased dendritic arbor of larger MNs seen in past studies and in the present study, and the consequent increase in relative capacitance of large soma surface area MNs to smaller soma surface area MNs is entirely consistent with the Henneman's size principle (Henneman, ; Henneman et al, ; Somjen et al, ; Cullheim and Ulfhake, ; Cullheim et al, ; Heckman and Enoka, ; Fogarty and Sieck, ).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, the dendritic length and membrane surface area is larger in F compared to S type motor units (Cullheim et al, ; Leroy et al, ). The capacitance of MNs is directly related to their orderly recruitment, where smaller surface area MNs of low capacitance require less unitary synaptic input to shift the membrane potential to discharge threshold, compared to larger MNs—the size principle (Henneman, ; Henneman et al, ; Somjen et al, ; Sieck and Fournier, ; Heckman and Enoka, ; Fogarty and Sieck, ).…”
mentioning
confidence: 99%
“…In a recent study, we reported that in old Fischer 344 rats there is marked (∼25%) phrenic motor neuron (MN) loss compared with young rats (Fogarty, Omar, Zhan, Mantilla, & Sieck, ). This loss affects the larger phrenic MNs disproportionately (Fogarty et al., ), which are likely to innervate IIx and/or IIb fibres (Fogarty & Sieck, ; Sieck, ; Sieck & Fournier, ) most affected by sarcopenia. Thus, it is likely that there is a denervation of DIAm fibres in sarcopenic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, in old age, resilience of the force‐generating capacity of the DIAm to accomplish ventilatory behaviours ranging from eupnoea to airway occlusion without fatigue is essential to sustain life (Belman & Sieck, ; Fogarty & Sieck, ; Mantilla & Sieck, ; Sieck, ; Sieck & Fournier, ). Previously, we reported a model for DIAm motor unit recruitment to accomplish P di generation across a range of motor behaviours (Fogarty, Mantilla, & Sieck, ; Mantilla & Sieck, ; Sieck, ; Sieck & Fournier, ).…”
Section: Discussionmentioning
confidence: 99%
“…The diaphragm muscle falls within the fascial continuum. Breath is part of a concept of symmetry, that is, maximum capacity adaptive to multiple functional questions in a defined biological context [25]. The act of breathing determines and defines our holobiont: how we react and who we are.…”
Section: Figure 1: the Statue Of The "Busto DI Donna Velata" By The Smentioning
confidence: 99%